The role of the mediterranean fruit fly, Ceratitis capitata, in Botrytis bunch rot of grape - Engelbrecht, Rene (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric)--University of Stellenbosch, 2002.